PERANCANGAN DAN IMPLEMENTASI WIDE AREA NETWORK (WAN) DENGAN IP VPN STUDI KASUS : PT. MDPU FINANCE - Siti Nur Khasanah (Jurnal Techno Nusa Mandiri, 2014)
In this time Data Communications have very required by business sector, especially company in the business sector having many branches in Indonesia or other states. In this time a lot of company integrating its information system which centrally like Enterprise Resources Planning ( ERP), Customer Relationship Management (CRM). Technological of Wide Area Network (WAN) become the solution for the communications of its data, there is a lot of solution which on the market service provider access to connect the this Wide Area Network, like a solution of Leased Channel, VSAT, DSL, etc. The solution of Virtual Private Network ( VPN) one solutions of the service provider and now selected by the company, because can become the peaceful and cheap alternative for the communications of its data WAN company. VPN of a technology WAN overcome in public network of Interne,t but its data is wrapped, encryption and overcome by tunneling at the time transmission on the Internet. VPN represents the alternative solution which can be selected by the company for the interconnection of to other offices.